Increased CO2 and light intensity regulate growth and leaf gas exchange in tomato. Issue 3 (16th August 2019) - Pan, Tonghua; Wang, Yunlong; Wang, Linghui; Ding, Juanjuan; Cao, Yanfei; Qin, Gege; Yan, Lulu; Xi, Linjie; Zhang, Jing; Zou, Zhirong
Abstract : Carbon dioxide concentration (CO2 ) and light intensity are known to play important roles in plant growth and carbon assimilation. Nevertheless, the underlying physiological mechanisms have not yet been fully explored. Tomato seedlings ( Solanum lycopersicum Mill. cv. Jingpeng No. 1) were exposed to two levels of CO2 and three levels of light intensity and the effects on growth, leaf gas exchange and water use efficiency were investigated. Elevated CO2 and increased light intensity promoted growth, dry matter accumulation and pigment concentration and together the seedling health index. Elevated CO2 had no significant effect on leaf nitrogen content but did significantly upregulate Calvin cycle enzyme activity. Increased CO2 and light intensity promoted photosynthesis, both on a leaf‐area basis and on a chlorophyll basis. Increased CO2 also increased light‐saturated maximum photosynthetic rate, apparent quantum efficiency and carboxylation efficiency and, together with increased light intensity, it raised photosynthetic capacity. However, increased CO2 reduced transpiration and water consumption across different levels of light intensity, thus significantly increasing both leaf‐level and plant‐level water use efficiency. Among the range of treatments imposed, the combination of increased CO2 (800 µmol CO2 mol −1 ) and high light intensity (400 µmol m −2 s −1 ) resulted in optimal growth and carbon assimilation. We conclude that the combination of increased CO2 and increased light intensity worked synergistically to promote growth, photosynthetic capacity and water use efficiency by upregulation of pigment concentration, Calvin cycle enzyme activity, light energy use and CO2 fixation. Increased CO2 also lowered transpiration and hence water usage.